Theories and narratives : reflections on the philosophy of history (Polity press, 1995)
Explores the relationship between social theory and historical writing. Its aim is to establish the contribution that theory can make to understanding the past. Pursuing this objective, Alex Callinicos critically confronts a number of leading attempts to reconceptualize the meaning of history, including Francis Fukuyama's rehabilitation of Hegel's philosophy of history and the postmodernist efforts of Hayden White and others to deny the existence of a past independent of our representations of it. In these cases philosophical arguments are pursued in tandem with discussions of historical interpretations of, respectively, Stalinism and the Holocaust. Leading theories of history - Marx's and Weber's - are then critically compared in the context of the work of recent writers such as Michael Mann, W.G. Runciman, and Robert Brenner. Finally, the politics of historical theory is explored in a discussion of Marxism's claims to be a universal theory of human progress. Swimming against the tide of contemporary fashion, Theories and Narratives seeks to rebut the claim made by many postmodernists that Marxism is inherently Eurocentric in both its conceptual structures and its political practice. Marx's project of human emancipation, it concludes, still defines our political horizons.